The The Importance of Regional Triangular - India-Pakistan-Afghanistan and Russian Interests in the Region - Alaverdov, Emilia (Journal of Education Culture and Society, 2022)
Aim. The paper aims to analyze the importance of such tangled triangular as India-Pakistan-Afghanistan and their impact over the whole Asia and its regional stability and security. The already complex region is complicated by interference of such great powers as Russia and pursuing its interests in the whole regional politics and each country separately. The paper examines the strategic interests and the level of cooperation and influence of India in Afghanistan and its implications for Pakistan.Methods. The study mainly is based on the following research methods: descriptive, analysis and document analysis, and analytical. The paper is based on the books, scientific papers, studies and researches conducted by the field’s researchers. Results. We can claim that the work clearly describes the significant role of India that makes its presence justified there to achieve its broader aims via Afghanistan. Although there will remain a sizeable role of US presence in Afghanistan, however, India is providing local socio-economic infrastructure and civil, military, and political services to promote peace and security in the war-torn country, which represents a threat and anxiety for the whole region.Conclusion. Regional cooperation between the five landlocked Central American republics, Afghanistan, Iran, and Pakistan opens up new directions and opportunities for the development of trade and economic relations. The Central Asian republics show great interest in the establishment of transport corridors through Afghanistan with access to the warm seas of the Arabian Sea and the Persian Gulf. Iran and Pakistan are developing their ports in anticipation of increased exports/imports and increased transit of goods.Keywords: Russia, India, Pakistan, Afghanistan, Asia, region, neighborhood, politics